The effect of oral bisphosphonates on acute kidney injury, gastrointestinal events and hypocalcaemia in patients with chronic kidney disease - Robinson, D; Ali, M; Pallares, N; Tebe, C; Cooper, C; Abrahamsen, B; Caskey, F; Ben-Shlomo, Y; Judge, A; Javaid, M; Diez-Perez, A; Prieto-Alhambra, D (Springer London, 2018)
Oral bisphosphonates (oBP) are contraindicated in patients with severe chronic kidney disease (CKD), but there is a lack of data on safety in this area. We aimed to study the association between oBP use and risk of acute kidney injury (AKI), gastrointestinal events (GIE) and hypocalcaemia (HC) in patients with moderate-severe CKD.